1)

slope = 2, point (1, 6)

(y - 6) = 2(x - 1)

y - 6 = 2x - 2

y = 2x + 4

2)

slope = -1/5, point (5, 4)

(y - 4) = (-1/5)(x - 5)

y - 4 = (-1/5)x + 1

y = (-1/5)x + 5

3)

slope = 4/3, point (12, 1)

(y - 1) = (4/3)(x - 12)

y - 1 = (4/3)x - 16

y = (4/3)x - 15

4)

slope = 0, y-intercept -3

y = -3

5)

slope = 2, point (-3, -10)

(y + 10) = 2(x + 3)

y + 10 = 2x + 6

y = 2x - 4

6)

slope = 1/2, point = (-2, 4)

(y - 4) = (1/2)(x + 2)

y - 4 = (1/2)x + 1

y = (1/2)x + 5

7)

slope = 5/4, point (4, -8)

(y + 8) = (5/4)(x - 4)

y + 8 = (5/4)x - 5

y = (5/4)x - 13

There, you have your lines

slope = 2, point (1, 6)

(y - 6) = 2(x - 1)

y - 6 = 2x - 2

y = 2x + 4

2)

slope = -1/5, point (5, 4)

(y - 4) = (-1/5)(x - 5)

y - 4 = (-1/5)x + 1

y = (-1/5)x + 5

3)

slope = 4/3, point (12, 1)

(y - 1) = (4/3)(x - 12)

y - 1 = (4/3)x - 16

y = (4/3)x - 15

4)

slope = 0, y-intercept -3

y = -3

5)

slope = 2, point (-3, -10)

(y + 10) = 2(x + 3)

y + 10 = 2x + 6

y = 2x - 4

6)

slope = 1/2, point = (-2, 4)

(y - 4) = (1/2)(x + 2)

y - 4 = (1/2)x + 1

y = (1/2)x + 5

7)

slope = 5/4, point (4, -8)

(y + 8) = (5/4)(x - 4)

y + 8 = (5/4)x - 5

y = (5/4)x - 13

There, you have your lines